Angiographic Studies of Coronary Artery Disease in Dhulikhel Hospital - Koju, R; Humagain, S (Nepalese Heart Journal, 2013)
Background Coronary Artery Diseases (CAD), one of the the leading causes of death, is increasing globally. The number of CAD is also increasing in Nepal. Dhulikhel Hospital is also providing cardiovascular services to populations from semiurban and rural population of mid region of country. It started coronary angiography services from April 2012. This paper aims to analyze pattern of coronary artery occlusion in patients undergoing coronary angiography during April to September months of 2012. Methods There were a total of 36 cases of diagnostic angiography and coronary interventions done in Dhulikhel Hospital from April to September 2012. Among them 32 cases of coronary angiography done for Acute Coronary Syndrome and Stable Angina, were analyzed using SPSS 17. Results Males were higher in number than females and majority of the patients were above 55 years. Out of 32 cases, 13 (40.6%) had Acute Coronary Syndrome (ACS) and 19(59.4%) had Stable Angina. Six out of 32 were found to have normal coronaries. One patient with ACS had normal coronary. Out of all the patients with coronary stenosis, four had left main disease, 14 had LAD stenosis, 7 had LCX stenosis and 12 patients had RCA stenosis. Thirteen had severe coronary stenosis. Nine out of 12 ACS patients had more than one coronary artery involved, which is significantly higher than the stable angina group (P<0.01). Severe stenosis was found to be more common in ACS group (p<0.001) when compared to the stable angina group. Conclusion Coronary angiography is a useful diagnostic and therapeutic tool for CAD. Coronary status is significantly different in ACS and stable angina. ACS has more chance of having multivessel stenosis whereas stable angina has single vessel, less severe or normal coronaries. Severity of stenosis is also high in ACS than in stable angina. DOI: http://dx.doi.org/10.3126/njh.v9i1.8348 Nepalese Heart Journal Vol.9(1) 2012 pp.43-46